Effects of distal radial access vs conventional radial access in patients undergoing coronary angiography and/or intervention: a meta-analysis of randomised trials. (3rd October 2022) - Condello, F; Rao, S; Maurina, M; Sturla, M; Jolly, S; Pancholy, S B; Bertrand, O; Lefevre, T; Condorelli, G; Stefanini, G G S; Reimers, B; Valgimigli, M; et al.
Abstract: Background: Recently the distal radial access (DRA) technique has been introduced for coronary angiography and intervention as an alternative to the conventional radial access (RA). Purpose: The aim of this study was to provide a quantitative appraisal of the effects of DRA vs conventional RA for coronary angiography with or without intervention. Methods: The PubMed, Embase, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov databases were searched for randomised clinical trials (RCT) comparing DRA versus RA for coronary angiography and/or intervention. Data were pooled by meta-analysis using a random-effects model. The number of patients needed to treat for an additional beneficial outcome (NNTB) and the number needed to treat for an additional harmful outcome (NNTH) were calculated. The primary endpoint was radial artery occlusion (RAO) at the longest available follow-up. Additional secondary outcomes were assessed. Results: A total of 13 RCT including 4, 901 patients were identified and included in the final analysis. Coronary angiography alone was performed in 3 studies, percutaneous coronary intervention was performed in a variable proportion of patients ranging from 24% to 100% across studies. Study population included patients with chronic coronary syndrome in the large majority, and the proportion of acute coronary syndrome ranged from to 31% to 100% across studies. Compared with RA, DRA was associated with a significant lower risk of RAO, either detected at the longest follow-up (risk ratio [RR]: 0.36; 95% CI: 0.23 to 0.58; p<0.001, NNTB = 24.5), or in-hospital (RR: 0.32; 95% CI: 0.18 to 0.57; p<0.001, NNTB = 21.5), as well as Early discharge after transradial stenting of coronary arteries (EASY) Scale ≥ II hematoma (RR: 0.46; 95% CI: 0.22 to 0.97; p=0.04, NNTB = 66). By contrast, DRA was associated with a higher risk of access site crossover (RR: 3.43; 95% CI: 1.88 to 6.25, p<0.001, NNTH = 10), a longer time for radial artery puncture (standardized mean difference [SMD]: 3.56; 95% CI: 0.96 to 6.16; p<0.001), and sheath insertion (SMD: 0.38; 95% CI: 0.11 to 0.65, p=0.006), and a higher number of puncture attempts (SMD: 0.59, 95% CI: 0.48 to 0.69, p<0.001). A meta-regression analysis showed that increasing age in the RA group was associated with a reduced effect of DRA, compared with RA, on the risk of RAO. No significant effect of other variables such as the prevalence of female sex, diabetes, smoking status, acute coronary syndrome, and percutaneous coronary intervention was found. Conclusions: Compared with RA, DRA is associated with lower risks of RAO and EASY ≥ II hematoma, but requires longer time for radial artery puncture and sheath insertion, more puncture attempts and a higher access site crossover. Funding Acknowledgement: Type of funding sources: None.